2019
DOI: 10.21203/rs.2.10737/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of Affecting Factors on Patient Safety Culture in Public and Private Hospitals in Iran

Abstract: Background: Patient safety culture is one of the main components of the quality of health services and is one of the main priorities of health studies. Considering the importance of this issue, this study aimed to determine and compare the views of health care staff on the patients’ safety culture and impact of effective factors on patient safety culture in public and private hospitals in Tehran, Iran. Methods: This cross-sectional study was carried out on a sample of 1203 health care workers employed in three… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 20 publications
2
10
0
2
Order By: Relevance
“…3 Positive response rate of this study showed much better results when compared to developed countries such as 60% to 80% in Norway, USA, Egypt and China. 13 The dimensions, "Personal attitude to Patient safety" and "Personnel influence over the safety", showed highest positive response among all cadres (88% and 67%) respectively.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…3 Positive response rate of this study showed much better results when compared to developed countries such as 60% to 80% in Norway, USA, Egypt and China. 13 The dimensions, "Personal attitude to Patient safety" and "Personnel influence over the safety", showed highest positive response among all cadres (88% and 67%) respectively.…”
Section: Discussionmentioning
confidence: 94%
“…Is also provides a clear overview of the patient safety aspects that require more attention. 13,14,15 A number of researches have been conducted on patient safety in recent years. In current study, the four HCP's were included and all had different response rate on 5 dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…The workload that is not balanced with the number of nurses in the room as happened in Iran and Jordan affects the application of patient safety cultural values. Research conducted by Khoshakhlagh et al, (2019) describes the negative impacts of excessive shift work, namely reduced compliance and quality of patient safety, double fatigue from work shifts, and increased medical errors. This negative impact has a direct impact on the implementation of a patient safety culture when increases burnout.…”
Section: Discussionmentioning
confidence: 99%
“…The imbalance between the number of health workers and the workload has a negative impact on patients and nurses. The negative impacts of overwork are reduced compliance and quality of patient safety, double fatigue from work shifts, and increased medical errors (Khoshakhlagh et al, 2019).…”
Section: Organizational Factors In the Implementation Of Safety Culture 1 Leadershipmentioning
confidence: 99%
“…Ao verificar "O Aprendizado organizacional e melhoria contínua", é corroborado uma porcentagem alta nesta dimensão, o mesmo foi identificado em estudo realizado no Irã, com 79,77% de respostas positivas, apresentando-se como a melhor dimensão avaliada neste estudo (KHOSHAKHLAGH et al, 2019). Os bons resultados se devem aos programas de educação permanente desenvolvida por profissionais de saúde que buscam identificar a presença de uma cultura de aprendizagem, na qual os erros são notificados, averiguados e revertidos em alterações positivas que levam a melhorias da assistência, e mostrou-se como uma das melhores avaliações positivas.…”
Section: Dimensões Mensuráveis Pelo Hsopsc Artigos N (%)unclassified